2005
DOI: 10.1063/1.1849057
|View full text |Cite
|
Sign up to set email alerts
|

Precessional dynamics in microarrays of nanomagnets

Abstract: Time resolved scanning Kerr microscopy has been used to study the response of square Ni88Fe12∕Co80Fe20 bilayer elements to a pulsed magnetic field. Measurements were performed upon a square element of 6000nm size and upon 64, 120, 220, 425, and 630nm square elements that formed square arrays of about 4000nm total size. While the frequency of precession of the magnetization of the 6000nm element could be described with a macrospin model, the frequencies observed in the arrays of submicron size elements differed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…For example, the nonuniform demagnetizing field may lead to the spatial confinement and quantization of spin-wave modes on the nanometer length scale. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] For thin-film elements where the magnetization lies in plane, the magnitude of the static in-plane demagnetizing field and the nonuniformity of the total effective field acting upon the magnetization increase when the element aspect ratio ͑size to thickness͒ is reduced. This results in a richer mode spectrum and hence in a less uniform magnetic response to a pulsed magnetic field, which can be directly imaged in the case of micrometer sized magnetic elements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the nonuniform demagnetizing field may lead to the spatial confinement and quantization of spin-wave modes on the nanometer length scale. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] For thin-film elements where the magnetization lies in plane, the magnitude of the static in-plane demagnetizing field and the nonuniformity of the total effective field acting upon the magnetization increase when the element aspect ratio ͑size to thickness͒ is reduced. This results in a richer mode spectrum and hence in a less uniform magnetic response to a pulsed magnetic field, which can be directly imaged in the case of micrometer sized magnetic elements.…”
Section: Introductionmentioning
confidence: 99%
“…15 and 16 but have about five times greater total thickness, and hence are characterized by a greater nonuniformity of the static magnetization and the total effective field within the element. We found that the precessional mode spectra vary in a discontinuous and complicated fashion as the bias magnetic field is reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the spatial character of the magnetization dynamics in nanometer-sized elements cannot be directly studied by TRSKM, the lack of a spatial resolution can be circumvented by combining the measurement of the time domain response from arrays of nanomagnets with thorough micromagnetic modeling. [14][15][16] In this Brief Report, TRSKM measurements were used to investigate the magnetization dynamics near one end of a long rectangular ferromagnetic wire. By using the TRSKM as a submicrometer probe of the magnetization dynamics at different points on the wire, we recorded its time-and position-dependent responses to a pulsed magnetic field.…”
mentioning
confidence: 99%
“…The images of the dynamic magnetization acquired at fixed pump-probe time delays revealed irregular stripes lying perpendicular to the long axis of the wire. We interpret the stripe pattern in terms of a collective mode of the quasiperiodic system of ripple domains 17 14 To make pump-probe measurements, a transmission line structure with a 30 m track width and separation was deposited around the elements so that they experienced an out-of-plane pulsed magnetic field. The pulsed field had rise and decay times of about 70 ps and 2.2 ns, respectively, and a maxi-mum strength of about 0.9 mT and was uniform over the area of the sample to better than 1%.…”
mentioning
confidence: 99%